Cox-2 Expression In Chemical Induced Neuro-Differentiation Of Ng108-15 Cell - PRAWPAN SUWANAKITCH; SUKKID YASOTHORNSRIKUL (International Journal of Pharma and Bio Sciences, 2012)
The pathogenesis of Alzheimer’s disease is complicated and related to COX-2. The NG108-15 cell line is a neuronal cell line. COX-2 expression in chemical induced neuronal differentiation of NG108-15 cells was investigated. Neuritogenesis of NG108-15 cells was induced by treatment with 100 mM dibutyryl cAMP (Bt2cAMP) and 100 μM 12-o-tetradecanoyl-phorbol 13-acetate (TPA) for 3 days. Cellular morphology alteration was monitored microscopically; the level of COX-2 mRNA and protein expression was determined by RT-PCR and western blotting, respectively. The differentiated NG108-15 cells exhibited neuron-like morphology. Twenty four hours after induction, there was a transient up-regulation of both COX-2 mRNA and protein level. There was a slight increase in COX-2 mRNA level on day 2 of NG108-15 cells, without a significant different in COX-2 protein level. COX-2 mRNA and protein in NG108-15 cells were a transient up-regulation after differentiation by Bt2cAMP and TPA.